The third restriction–modification system from Thermus aquaticus YT-1: solving the riddle of two TaqII specificities. Issue 15 (12th July 2017) - Skowron, Piotr M.; Anton, Brian P.; Czajkowska, Edyta; Zebrowska, Joanna; Sulecka, Ewa; Krefft, Daria; Jezewska-Frackowiak, Joanna; Zolnierkiewicz, Olga; Witkowska, Malgorzata; Morgan, Richard D.; Wilson, Geoffrey G.; Fomenkov, Alexey; et al.
Abstract: Two restriction–modification systems have been previously discovered in Thermus aquaticus YT-1. TaqI is a 263-amino acid (aa) Type IIP restriction enzyme that recognizes and cleaves within the symmetric sequence 5′-TCGA-3′. TaqII, in contrast, is a 1105-aa Type IIC restriction-and-modification enzyme, one of a family of Thermus homologs. TaqII was originally reported to recognize two different asymmetric sequences: 5′-GACCGA-3′ and 5′-CACCCA-3′. We previously cloned the taqIIRM gene, purified the recombinant protein from Escherichia coli, and showed that TaqII recognizes the 5′-GACCGA-3′ sequence only. Here, we report the discovery, isolation, and characterization of TaqIII, the third R–M system from T. aquaticus YT-1. TaqIII is a 1101-aa Type IIC/IIL enzyme and recognizes the 5′-CACCCA-3′ sequence previously attributed to TaqII. The cleavage site is 11/9 nucleotides downstream of the A residue. The enzyme exhibits striking biochemical similarity to TaqII. The 93% identity between their aa sequences suggests that they have a common evolutionary origin. The genes are located on two separate plasmids, and are probably paralogs or pseudoparalogs. Putative positions and aa that specify DNA recognition were identified and recognition motifs for 6 uncharacterized Thermus -family enzymes were predicted.